Digital inverter welding machine and control operation system thereof - MA YUEZHOU; ZHAO XIAOJUN; LI CHENGWEN; YU XIAORONG; SHANG TIANDE; QIAN YONG (2013)
The utility model relates to an inverter welding machine, in particular to a control operation system which is simple in operation, convenient to use and can be supervised in real time, and a digital inverter welding machine comprising the control operation system. The control operation system comprises an operation panel (1) and a control circuit, wherein the control circuit comprises a digital control chip (2) which is used for processing signals and data, a display driving module (3) which is connected to the digital control chip (2), and a USB (universal serial bus) communication module (4) and a storage (5) respectively connected with the digital control chip (2); the USB communication module (4) is used for accessing a USB flash disk into the control circuit; a USB regulating module (6) is connected to the display driving module (3); and a display (7) and a USB interface (8) connected with the USB communication module (4) are arranged on the operation panel (1). The digital inverter welding machine and